Analysis of clinical and morphological parameters in patients with vulvar melanoma - E. V. Korzhevskaya; V. V. Kuznetsov; O. A. Zaspa; Yu. G. Payanidi (Опухоли женской репродуктивной системы, 2014)
The purpose of this study was to estimate the value of and to reveal the specific features of clinical and morphological parameters in pa- tients with vulvar melanoma. The study was based on the data obtained from the analysis of 40 vulvar melanoma patients treated at the N.N. Blokhin Russian Cancer Research Institute in the period January 1980 to December 2010.